Role of bile acids in overweight and obese children and adolescents - Giannini, Cosimo; Mastromauro, Concetta; Scapaticci, Serena; Gentile, Cristina; Chiarelli, Francesco (Frontiers in Endocrinology, 2022)
Bile acids (BAs) are amphipathic molecules synthetized in the liver. They are primary involved in the digestion of nutrients. Apart from their role in dietary lipid absorption, BAs have progressively emerged as key regulators of systemic metabolism and inflammation. During the last decade, it became evident that BAs are particularly important for the regulation of glucose, lipid and energy metabolisms. Indeed, the interest in bile acid role in metabolism homeostasis is further increased due to global public health increase of obesity and related complications and a large number of research postulate that there is a close mutual relationship between bile acid and metabolic disorders. This strong relationship seems to derive from the role of BAs as signalling molecules involved in regulation of a wide spectrum of metabolic pathways. These actions are mediated by different receptors and in particular nuclear farnesoid X receptor (FXR) and the Takeda G protein coupled receptor 5 (TGR5) which are probably the major effectors of BAs actions. These receptors activate transcriptional networks and signaling cascades controlling the expression and activity of genes involved in bile acid, lipid and carbohydrate metabolism, energy expenditure, and inflammation. The wide connection existing between BAs and metabolic disorders offers the possibility that modulation of BAs could be used as a therapeutic approach for the treatment of metabolic diseases, including obesity itself. The aim of this review is to describe the main physiological and metabolic actions of BAs, focusing on its main signalling pathways which are important in the regulation of metabolism and might provide the development of new bile acid–based treatments for metabolic diseases.